Petrologia das sucessões vulcânicas do Grupo Colíder na região entre Guarantã do Norte e a Serra do Cachimbo, Mato Grosso, Brasil - Santos, Fernanda Silva (2018)
The Colider Group ignimbrites and rhyolites, located between Guarantã do Norte and Serra do Cachimbo, are derived from a felsic magmatism with a wide spatial distribution at the Alta Floresta Gold Province (AFGP). The geological mapping and petrographic studies allowed to individualize three volcanic successions of the Colider Group at the area, named Inferior (Sinf), Intermediate (Sint) and Superior (Ssup). This dissertation aims to study, from the faciological, lithochemical and geochronological data, the primary volcanic successions (inferior and superior). The Sinf characterizes by its abundance in ignimbrites and primary pyroclastic rocks, such as surge deposits, with subordinated effusive rocks. The occurrence of crystal-rich ignimbrites restricted to the Sinf and with low content of glassy fragments indicates the eruption of highly crystalized magmas, whose pyroclastic deposits were submitted to elutriation processes during the transport and deposition. The Ssup is mainly composed by rhyolites and effusive trachytes and, subordinately, by reomorphic ignimbrites. The lithologies are characterized by the low content of phenocrysts and lithic fragments that indicate the eruption of poorly crystalized magmas. The petrographic differences observed between the two sucessions indicate variations of composition and eruption style in the generation of the different volcanic deposits. It is noted that the magmas that generated the volcanic rocks of the Sinf had a subsolvus character. The Ssup rocks present, dominantly, mineralogy indicating a hypersolvus character at the magma crystallization. This characteristic can be indicating a variation of the fluid pressure conditions inside the magmatic chambers that generated this magmatism. Regarding the chemical composition of the volcanic rocks from the two sucessions, it is noticed that both have a metaluminous to slightly peraluminous character and affinity with A2-type magmas. The distribution patterns of the major and trace elements in multi-element diagrams are similar and characterized by negative anomalies of Ba, Nb, Ta, Sr, P, Ti and Eu, with a horizontalized pattern of HREE. The rocks from the Ssup have an essentially ferrous character, while the Sinf rocks have a character varying from magnesian to ferrous. The U-Pb isotopic data (LA-ICPMS) obtained in zircon crystals of a Sinf rhyolite indicate a crystallization age of 1810±9 Ma, interpreted as the Inferior Sucession age. One of the hypotheses that may be suggested to the generation of those volcanic sucessions is that the petrographic, lithochemical, and geochronological differences indicate the occurrence of two different magmatic events, one of ~1,81 Ga and another of ~1,76 Ga, derived from similar magmatic sources, due to lithochemical similarities. The second hypothesis is that both of the sucessions belong to the same magmatic event, which occurred from 1,81 Ga to 1,76 Ga, and that the slightly petrographic and lithochemical differences represent a small variation of the magmatic source and the crystallization conditions inside the magmatic chamber.